Haematological and blood biochemical profile of spotted deer (Axis axis) reared in semi-captive environment - SAHOO, A; ARORA, B M (The Indian Journal of Animal Sciences, 2014)
Haematologieal and blood biochemical values were measured in 4 sedated chital deer (Axis axis) stags ( 1-2 years of age) reared in semi-captive environment to compare as reference values vis-a-vis domestic small ruminants for assessing their nutritional and health status. Haemoglobin, haematocrit (PCV), total erythrocyte count and total leukocyte count were measured 10 show 9,6±10.97 g/dl, 34±0.6%, 13.0±0.8 x 106 and 4.4±0.3 x 103 respectively. The mean corpuscular volume, mean corpuscular haemoglobin and mean corpuscular hemoglobin concentration were found out to be 26. 7± 1.2 µ3, 7.4±0.4 µg,and 27.8±2.3% respectively. The red cell observed to he microcytic type in spotted deer. Amongst the different leukocytes neutrophils predominated.(52± 1.7%) over lymphocytes (44±1.3%) compared to other small ruminant species. Plasma glucose, urea, serum total protein and albumin concentrations were 62±:7 mg/dl, 10.1±:0.8 mg/dl, 8.2±0.15 g/d/ and 4.7±0.33 g/dl respectively. Serum calcium and phosphorous showed normal value and the enzymes, viz. aspartate amino-transaminase and alanine amino-transaminase, were measured 66±5 and 40±3 IU/l. Stress of handling due to chemical immobilization and restraint may have induced some alteration in these haemato-biochemical parameters, which is difficult to be eliminated and similar ohservations may be compiled for reference in captive or semi-wild deer species.